Challenges of Multidrug-Resistant Tuberculosis Meningitis: Current Treatments and the Role of Glutathione as an Adjunct Therapy - Mohammad J. Nasiri; Kabir Lutfy; Vishwanath Venketaraman (Vaccines)
Multidrug-resistant tuberculosis (MDR-TB) poses a significant global health threat, especially when it involves the central nervous system (CNS). Tuberculous meningitis (TBM), a severe manifestation of TB, is linked to high mortality rates and long-term neurological complications, further exacerbated by drug resistance and immune evasion mechanisms employed by Mycobacterium tuberculosis (Mtb). Although pulmonary TB remains the primary focus of research, MDR-TBM introduces unique challenges in diagnosis, treatment, and patient outcomes. The effectiveness of current treatments is frequently compromised by poor CNS penetration of anti-TB drugs and the necessity for prolonged therapy, which often involves considerable toxicity. This review explores the potential of cytokine-based adjunct immunotherapies for MDR-TBM, addressing the challenges of balancing pro-inflammatory and anti-inflammatory signals within the CNS. A central focus is the prospective role of glutathione, not only in reducing oxidative stress but also in enhancing host immune defenses against Mtb’s immune evasion strategies. Furthermore, the development of vaccines aimed at upregulating glutathione synthesis in macrophages represents a promising strategy to bolster the immune response and improve treatment outcomes. By integrating glutathione and innovative vaccine approaches into MDR-TBM management, this review proposes a comprehensive strategy that targets Mtb directly while supporting immune modulation, with the potential to enhance patient outcomes and reduce treatment related adverse effects. We underscore the urgent need for further research into adjunctive therapies and immunomodulatory strategies to more effectively combat MDR-TBM.